Al-Walad Lil-Firasht Vs Teknologi DNA: Menyusun Kaidah Pembuktian Berbasis Hadist (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
The purpose of this research is to find out the legal basis in the science of hadith or Islamic law and positive law related to DNA testing which is used as a strong argument for determining the legal certainty of child lineage and how to resolve the problem of child lineage in Indonesia and Islam. In the research process used is normative research and library research with a legislative approach taken from positive law and Islamic legal sources, namely the Qur'an and the hadith approach as a basis for legal theory. The resulting research study that DNA testing can resolve the uncertainty of abak lineage and DNA test results can be used as proof of determining a child's lineage to his father. In the teachings or regulations of Islamic law, there are four methods used in determining lineage in accordance with the terms and conditions of the application of the four methods, namely; al-firasy, al-iqrar, al-bayyinah, and al-Qiyafah. With the development of today's technology, the four methods have been developed through cutting-edge technology as a medium for tracing a person's lineage to obtain justice and benefit. From a positive Indonesian legal perspective, DNA testing has been recognized as a means of proving parentage. Therefore, children born as victims of rape, marriages not officially registered by the Office of Religious Affairs (KUA), and marriages that took place secretly (in other words, under the table) can claim their rights as children, including child support and parentage, from their father.